GEOMETRIC EVALUATION OF ROADS ON MAJALENGKA-CIKIJING ROAD: A CASE STUDY OF PASUKAN SINDANGKASIH-JALAN CUCUK DALEM - Moch. Galih Pramadita; Andri Irfan Rifai (Fakultas Teknik Sipil dan Perencanaan, 2024)
Highways are one of the land transportation accesses to support human movement in driving and sending goods from one region to another. The geometric of the road is the building of the highway above the ground level both vertically and horizontally with the assumption that the ground surface is not flat. Horizontal alignment is often referred to as road situation or road alignment. The most critical part of the horizontal alignment is in corners, where centrifugal force pushes the vehicle out of the bend area. Superelevation is a slope A transverse slope at a bend that serves to offset the centrifugal force received by the vehicle when traveling through the bend at. The quantitative method can also be interpreted as a research method that looks at reality, symptoms, and phenomena that can be classified, are relatively fixed, concrete, observable, and measurable, and the relationship of symptoms is causal. Road evaluation in this study uses a design speed of 60 km/hour, with a road width of 3.5 m. Road evaluation was carried out using AutCAD® Civil 3D based on the contour data obtained. Based on the calculation results above, the Majalengka-Cikijing road is a hill road type. Then for the horizontal alignment with a speed of 60 km/hour, the results obtained from 11 horizontal alignments all belong to the Spiral-Cirle-Spiral alignment type.